Edukasi Literasi Keuangan dan Pengelolaan Risiko Finansial Bagi Ibu Rumah Tangga di Beji Depok - Yulia Armelia; Shafa Nur Amanda; Marina Deswari (SEWAGATI: Jurnal Pengabdian kepada Masyarakat, 2026)
Financial literacy is a strategic competency for households in maintaining economic stability amidst the rapid digitalization of financial services. However, easy access to financial products carries potential risks, including excessive consumer debt, illegal online loans, digital fraud, and inadequate financial planning. This community service program aims to enhance the capacity of housewives regarding financial protection, family financial management, emergency fund planning, responsible debt management, and awareness of illegal financial services. The activity was conducted in Beji District, Depok City, involving 22 participants through educational lectures, interactive discussions, and Q&A sessions. A post-activity questionnaire was used to evaluate participants' understanding and responses. The results demonstrated significant improvements in household budgeting, emergency fund preparedness, responsible debt management, and awareness of digital financial fraud risks. The program demonstrates that community-based financial literacy education is effective in strengthening household financial resilience.